The Impact Of Using Doodle Technique On Improving The Performance Of Reading Comprehension Of High School Students' (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study investigated the effect of using the doodling technique on the reading comprehension of students and studied the significant differences. The research was conducted with 60 female 5th High School Students, (N=30) for an experimental group and (N=30) for a control group. Doodle strategies were implemented with the experimental group. Paired-Sample T-Test was used. The pre-test and post-test mean scores of students in the experimental group were compared to the scores of the control group using the independent t-test. The findings of the study revealed that the application of Doodle strategies is very significant in increasing the learners’ levels. Therefore, it could be proved that the doodle strategy affected EFL Students' scores and increased a lot.